Interactive Digital Media Based on VoD to Improve Understanding of K3l and PPE among Students with Mild Intellectual Disabilities - Pina Nofalia; Megaiswari Biran Asnah; Nurhastuti (Universitas Pendidikan Ganesha, 2025)
Limited understanding of occupational safety, health, and environmental elements among students increases the risk of accidents both at work and in daily life. This study aimed to develop and evaluate the effectiveness of interactive digital learning media based on Video on Demand (VoD) in enhancing the understanding of students with mild intellectual disabilities regarding occupational safety, health, environment, and the use of personal protective equipment (PPE). This research employed a Research and Development (R&D) approach using the ADDIE model. The research subjects included one learning media expert, three content experts, three teachers, six parents, and ninth-grade students with mild intellectual disabilities as trial participants. Data were collected through interviews, observations, questionnaires, and tests, and were analyzed descriptively and qualitatively. Expert assessments yielded scores of 97.7% (media expert) and 88.5–90.6% (content experts), while practicality tests by teachers and parents scored 93% and 92.58%, respectively, indicating the media’s feasibility. Quantitative effectiveness tests showed an average pre-test score of 2.67 and a post-test score of 7.83. Analysis using the Wilcoxon signed-rank test produced a p-value <0.05, demonstrating a significant improvement in all students’ understanding of occupational safety, health, and PPE. It is concluded that the interactive digital VoD-based media is effective in enhancing the understanding of students with mild intellectual disabilities and provides a valuable contribution to the development of inclusive vocational learning tools adaptable to students’ special needs.